Dimensi Teologis dan Pedagogis Pertobatan Santo Dismas: Model Pendidikan Iman Katolik di Era Modern - Yanto Sandy Tjang; Mayong Andreas Acin; Laurentius Prasetyo; Florensius Sutami; Felisitas Yuswanto (Jurnal Penelitian Pendidikan Agama Katolik, 2026)
This article examines the conversion of Saint Dismas in Luke 23:39–43 to uncover its theological meaning and relevance for contemporary Christians. Using a qualitative, descriptive-analytical literature review, it analyses the biblical text through a hermeneutical approach alongside recent theological scholarship. The findings show that Dismas’s conversion comprises three key elements: awareness of sin, confession of faith in Jesus, and acceptance of saving grace, which form a basic paradigm for understanding the Sacrament of Penance and Christian renewal of life. Jesus’ promise, “Today you will be with Me in Paradise,” affirms the universality and immediacy of God’s saving grace that transcends time and social status. These insights speak to Christians today, who face individualism, moral relativism, and a tendency to postpone conversion. Saint Dismas thus inspires Church and faithful to practice ongoing repentance, open themselves to God’s forgiveness, and foster a culture of mercy in personal, family, and social life. Keywords: Conversion; Pastoral Theology; Sacrament of Penance; Saint Dismas; Saving Grace.